It's uphill all the way to the top, regardless of mountain size: RepositBox's search for a suitable path to go to market. Issue 1 (11th July 2016) - Ensign, Prescott C.; Robinson, Nicholas P.
Abstract : Purpose: This case aims to illustrate the hurdles that a young venture might experience in the early stages of its life cycle and showcase how managers must use ingenuity to climb over obstacles. Design/methodology/approach: The case is based on interviews with the founders and additional secondary data. Findings: RepositBox, a Canadian-based provider of credentials verification solutions, is a new venture coping with the challenges posed by the introduction of its innovative new product to the marketplace. Originality/value: The case is suitable for use in undergraduate or graduate courses in new venture creation, entrepreneurial marketing and launching a technology-based enterprise.